Generalized lichen striatus. Case report. - Betto, P.; Gennari, E. (European Journal of Pediatric Dermatology, 2003)
A 6-year-old girl presented a bilateral, diffuse, self-healing eruption with mosaic distribution according to the Blaschko lines. Generalized lichen striatus was diagnosed. The latter is the most typical acquired, inflammatory skin disorder, distributed according to the Blaschko lines, thus justifying the alternative name blaschkitis.